Analisis Nilai Absorbansi dalam Penentuan Kadar Flavonoid untuk Berbagai Jenis Daun Tanaman Obat - Neldawati Neldawati (PILLAR OF PHYSICS, 2013)
This research backgrounded by to the number of drug crop reported to contain compound of antioksidan in gross. Effect of antioksidan at plant caused by the existence of compound of fenol like flavonoid, and acid of fenolat. Flavonoid is an compound of fenolik biggest found by in potential nature as antioksidan and have bioaktivitas as drug. This compound can be found by at bar, leaf, fruit and flower. This research represent research of done/conducted experiment in Physics laboratory that is in Material laboratory and Biophysics, and also Chemical laboratory of FMIPA, UNP. Variables which is determined in this research that is used as by drug crop leaf type is free variable consisting of leaf of Rhaphidophora pinnata (L.f.), Piper crocatum Ruiz, Annona muricata Linn and leaf of Sauropus androgynus (L.) Merr, absorbance value as variable tied and used as by leaf mass is control variable. Each;Every sampel measured by absorbance value use spectrophotometer of Uv-Vis. Of absorbance value can be counted/calculated by rate value of flavonoid from various drug crop leaf type. From result of measurement of absorbance value got that leaf of sirih red have biggest absorbance, while absorbance of terendah there are at leaf of katuk. Of the absorbance can know by rate of flavonoid sampel. Rate of Flavonoid at each crop leaf type medicinize different each other. For the leaf of Rhaphidophora pinnata (L.f.) have rate of flavonoid about 26,7137 µ g / ml, for the leaf of Piper crocatum Ruiz have rate of flavonoid about 39,3778 µ g / ml. For Annona muricata Linn to have rate of flavonoi about 27,5027 µ g / ml and for the leaf of Sauropus androgynus (L.) Merr have rate of flavonoid about 13,1101 µ g / ml. Keywords: Absorbance, Flavonoid, Leaf Medicinize and Spektrofotometri UV-Vis